PERBEDAAN PERSEPSI MAHASISWA AKUNTANSI BERDASARKAN GENDER TENTANG TEKNOLOGI INFORMASI YANG HARUS DIKUASAI OLEH AKUNTAN (Studi Pada Mahasiswa Akuntansi STIE Nasional Banjarmasin) - Ferra Maryana; Wibisono Tri Hastomo (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2016)
Abstract, This research aimed to give empirical evidences about the difference perception between man and woman of capability of information technology which accountant had to mastersed. The variables in this study were capability of information technology which accountant had to mastered gender. The population in this was research the accounting students in STIE Nasional Banjarmasin. The data collected from the output of questionnaires which gived to the respondents. The samples technique used purposive sampling with 100 samples. The research gived empirical evidences that there were no different between man and wowan abaout their perception of capability of information technology which accountant had to mastered.